Conflict in the Israëli Industrial Relations System: A Critical Description - Chermesh, Ran (Relations industrielles / Industrial Relations, 1981)
The paper examines the Israeli industrial relations System at two levels: national and organizational. It utilizes Eldridge 's formulation of Dunlop's (1958) concept of the industrial relations system.